Interface formation and interlayer factors of three-dissimilar-metal layers joint in impact welding. (October 2021) - Meng, Zhenghua; Zhou, Rui; Gong, Mengyuan; Guo, Wei; Liu, Wei; Huang, Shangyu
Abstract: Impact welding joint with an inserting interlayer can be used to improve the weldability of hard-to-weld metal pairs. However, the formation mechanism of wavy interface during welding and the prediction of the wave interface in three-dissimilar-metal layers remain unclear. In this study, finite element method (FEM) and smoothed particle hydrodynamics (SPH) consolidation algorithm was used to simulate the joining process of the wavy interface of three-dissimilar-metal layers in impact welding. Results show that the three-layer impact welding sequentially forms three welding zones (α, β, γ). The welding process consists of three stages: first, the flyer impacts the interlayer at subcenter (zone α); second, the interlayer impacts the target (zone β); and third, the flyer impacts the reflected interlayer (zone γ). The formed zone γ increases the area of flyer– interlayer interface. The increase in top interval enlarges the waveform amplitude in zone α but reduces it zones β and γ. Meanwhile, the increase in bottom interval only enlarges the amplitude in zone β. The thick interlayer can also form a high waveform amplitude of three wavy zones. When both interfaces can form welding zones, a thick interlayer leads to the growth of effective welding area within the right range.